SOCIO-EDUCATIONAL CONTEXTS OF THE QUALITY OF LIFE OF SENIORS - Jagielska, Katarzyna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
One of the most important phenomena of the changing world is aging of population. With the growing number of older people it is necessary to focus on this part of population. It is also important to allow seniors active participation in social life. The aging population provides us with many interesting materials for scientific consideration and one of them is the socio-educational contexts of the seniors' quality of life. The purpose of this study is to analyse the theoretical basis of quality of life of seniors and to highlight the relevant factors affecting the quality of life in relation to older people. In this paper it is shown how education can affect the quality of life of older people not only in terms of acquiring new knowledge, but also in the context of establishing social relations and social activation. The study focous on a theoretical study and an attempt to analyse the available data on the participation of Polish seniors in education.